Analyzing Changes in Students’ Media Writing Self-Perceptions During a Writing-Intensive Course - Cara Lawson; Whitney Whitaker; Courtney Meyers (Journal of Applied Communications, 2021)
Regardless of academic discipline or future career responsibilities, college students are challenged to meet future employers’ demand for strong communication skills. However, becoming an effective, professional writer is a struggle for many college students. Based upon concepts of writing self-efficacy and writing apprehension, the Media Writing Self-Perception (MWSP) scale was administered to undergraduate students in a writing-intensive agricultural communications course to evaluate differences in writing self-perceptions as the semester progressed and to determine any relationships between MWSP scores and scores on assignments. Statistically significant differences were found in writing apprehension, self-efficacy, and elaborative/surface construct scores from the beginning of the semester to the end. A positive correlation was found between MWSP pretest and posttest scores and grades on major writing assignments, supporting the assertion that stronger self-perceptions of writing self-efficacy is related to improved writing overall. Students also reflected upon their MWSP scores, which revealed themes that illustrated variation in preferred styles of writing and highlighted the role of writing assignments in influencing their writing self-perceptions. This study supports the growing body of literature that indicates rigorous, diverse assignments are beneficial to improving writing skills and allowing time for reflection helps student writers understand how they can improve.
Keywords: college students; writing apprehension; writing self-efficacy; pedagogy